Separatist Creditors vs Preferred Creditors Rights in the Bankruptcy Case Based on the Decision of Constitutional Court of 2013 - Rilda Murniati; Desma Cahya Selvya (Universitas Lampung, 2019)
Workers are preferred creditors whose payment must take precedencein the bankruptcy of the company. Problems in practice occur in thecompany's assets as collateral for debt to separatist creditors so that workers'rights are ruled out. Therefore, workers submit applications for judicialreview of the Bankruptcy Law and Labor Law. This study is normativeresearch using primary legal materials, namely laws and case study decisionsthat are analysed qualitatively. The results of the study and discussiondetermined that the Bankruptcy Law and the Labor Law regulate the same asthe legal status of workers as preferred creditors who are entitled to prioritizepayment in the distribution of bankrupt assets strengthened by the results of ajudicial review in Decision of the Constitutional Court Number 67/PUUXI/2013 The right of workers to wages is prioritized and calculated fromcollateral objects which are the rights of separatist creditors. For this reason,curators with authority must share the right of separatist creditors andpreferred creditors with the principle of balance and justice so that all theassets of a bankrupt company can pay off the debts of its creditors